A non linear Full-FEM 3D model to describepile-soil interaction under static and cyclicloading conditions - Korres, Michail (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2018)
Deep foundations consist of a practical solutions when specific geotechnical constraints do not allow the use of shallow foundations for the support of the superstructure. Pile-soil interaction remains a complex problem strongly influenced by non-linear phenomena of unilateral friction of the interface, as well as soil behavior. Standard design methods are based on approximations and correlations with experimental results while the estimation of soil’s mechanical properties consists from it’s own quite an uncertain task. On this context, numerical analysis can be of important support for the design and analysis of geotechnical structures. A full-FEM 3D model with code aster is proposed for a soil-pile geotechnical structure. Interface behavior is modeled with the use of joint elements where Coulomb’s friction law control sliding. Non-linear behavior of soil is considered in an elasto-plastic framework adopting different soil modeling hypothesis. The proposed model is tested under different loading conditions axial/lateral, monotone or cyclic, and sensibility studies are examined so as to identify the impact of important parameters. A comparison with experimental results provides the validation of the proposed modeling strategy/strategies.